Dynamic self-regulation as an effective time management strategy for clinical nurses: A qualitative study. Issue 4 (August 2019) - Talebi, Mehdi; Ahmadi, Fazlollah; Kazemnejad, Anoshirvan
Abstract: Background: The concept of time management is well-recognized, but a few studies have investigated how people manage their time. However, we know that personal experience, sociocultural, and organizational background contribute to the select of time management strategies. Aim: To explore the clinical nurses' experiences of time management strategies. Design: Qualitative content analysis. Methods: Data was collected using purposive sampling from 17 clinical nurses. Data collection began using unstructured, in-depth face-to-face interviews and was continued as semi-structured. The interviews were recorded, transcribed verbatim and analyzed using the inductive content analysis approach proposed by Graneheim and Lundman (2004). Results: The clinical nurses managed time/tasks delegated to the nursing team through the dynamic self-regulation process involving workload estimation, foresight, compendious-orientation, self-working style and skill development, extra-role performance behaviors, selective choice of activities, seeking help from others, contingency division of labor, and discipline-orientation. Discussion: The work-shift was surrounded by uncertain conditions. In these conditions, the clinical nurses required more time management skills to provide maximum and high priority care based on a dynamic self-regulation process by the nursing team. Conclusion: Clinical nurses can manage their time/tasks and perform maximum and high priority tasks delegated to the nursing team by an optimal use of time, use of facilities and opportunities for saving time, extend available time, and prevent a waste of time based on the dynamic self-regulation process.